(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The objective of this paper is to discuss how national, collaborative programs based on the dissemination of good practices could effectively improve patient safety and be sustainable. The paper also aims at identifying some cross-system characteristics that would allow for a “safe practice program” to run successfully. Methods: The quality and safety of the healthcare services provided by the Italian healthcare system to its citizens are very heterogeneous. Therefore, a public agency – by government mandate – instituted a national program to improve patient safety. The model applied relies on a cyclic scheme for collecting, classifying and promoting the active dissemination of evidence-based safe practices throughout the network of healthcare providers. Results: The Italian program has been reviewed by the OECD as a key action to improve patient safety as the results are very encouraging in terms of both effectiveness and sustainability. Conclusion: In this paper we use the experience of the Italian Observatory on Good Practices for Patient Safety to corroborate and enrich the literature about improvement programs based on good practices. If specific conditions of responsiveness and accountability are met at all levels, these programs can be successful and sustainable. Furthermore, such programs could be easily adapted to other health care systems.